Orthostatic intolerance as a potential contributor to prolonged fatigue and inconsistent performance in elite swimmers - Petracek, L. S.; Eastin, E. F.; Rowe, I. R.; Rowe, P. C. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Athletic underperformance is characterized by fatigue and an inability to sustain a consistent exercise workload. We describe five elite swimmers with prolonged fatigue and athletic underperformance. Based on our work in myalgic encephalomyelitis /chronic fatigue syndrome, we focused on orthostatic intolerance as a possible contributor to symptoms.